BPSD patterns in patients with severe neuropsychiatric disturbances: insight from the RECAGE study: brief report - Cognat, Emmanuel; Sabia, Séverine; Fayel, Alexandra; Lilamand, Matthieu; Handels, Ron; Fascendini, Sara; Bergh, Sverre; Frisoni, Giovanni B.; Fabbo, Andrea; Tsolaki, Magdalina; Frölich, Lutz; Peters, Oliver; et al. (American journal of geriatric psychiatry, 2023)
Objective - Behavioral and psychological symptoms of dementia (BPSD) profiles vary depending on etiology in patients with mild-to-moderate BPSD. It is not known if similar differences exist in patients with severe BPSD. - Methods - We analyzed data collected at baseline in 398 patients with severe BPSD (NPI ≥ 32) and defined diagnosis of dementia (Alzheimer's disease [AD] 297; frontotemporal dementia [FTD] 39; Lewy body disease/Parkinsonian dementia [LBD/PD] 31; and vascular dementia [VD] 31) included in the European multicenter cohort RECAGE. - Results - Mean total NPI was 52.11 (18.55). LBD/PD patients demonstrated more hallucinations, more anxiety and more delusions than patients with other dementia. FTD patients had less delusions and more disinhibition than patients with other neurodegenerative disorders. These profiles overlapped partially with those reported in the literature in patients with less severe symptoms. - Conclusion - Patients with severe BPSD display different and specific profiles of neuropsychiatric symptoms depending on dementia etiology.
Online verfügbar: 23. April 2023, Artikelversion: 29. Juni 2023
Gesehen am 28.03.2024